Past and Future of Computer-Assisted Language Comparison in Practice (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2024)
Our blog "Computer-Assisted Language Comparison in Practice" goes into its seventh year. We reflect on the role the blog played in the past and present and new goals and concrete ideas for the future. The most drastic innovation we initiated is to turn the blog into an open journal, which means that all future and successively also past contributions will be archived in PDF format with digital object identifiers.
Keywords: editorial article; online publication; scientific blogging; scientific practice